Estudo comparativo da sobrevida entre pacientes com meduloblastoma operados em um centro de referência oncológica e outros hospitais - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
Medulloblastoma (MB) is the most common brain malignancy of childhood, repre-senting approximately 15-20% of all central nervous system (CNS) tumors that affect the pediatric population. The survival of children with medulloblastoma increases sig-nificantly when the combined treatment of surgery, radiotherapy and chemotherapy is used. The main objective of this study was to evaluate survival among patients diag-nosed with medublastoma operated in an oncology referral center (INCA/RJ – Insti-tuto Nacional de Câncer/Rio de Janeiro/RJ) in comparison with public and private hospitals that visit their patients for treatment. adjuvant (after surgery) for INCA. A retrospective cohort of both genders was described, with histopathological diagnosis of both medulloblastoma, ages between 3 and 18 years, enrolled in the Pediatric On-cology sector of the Instituto Nacional do Câncer/RJ (INCA/RJ). Most of the ethnici-ties described are the events that occurred between the years 2010 to 2021. Consid-ering the data of male cases, it is possible to verify that it is male (55.4%), and mixed with 43.1% and 44, 6% respectively. In addition, 95.4% of patients were selected for radiotherapy and 87.7% for chemotherapy. How many, patients operated at INCA/RJ showed a lifetime about how many life groups have no meaning about this referral center and disease overall survival time, about the majority between the two groups studied.
Keywords: Meduloblastoma; Análise de sobrevida; Pediatria; CNPQ:: CIÊNCIAS DA SAÚDE